Adjunct Digital Interventions Improve Opioid-Based Pain Management: Impact of Virtual Reality and Mobile Applications on Patient-Centered Pharmacy Care - Giravi, Hayam Y.; Biskupiak, Zack; Tyler, Linda S.; Bulaj, Grzegorz (Frontiers in Digital Health, 2022)
Digital therapeutics (DTx, mobile medical apps, software as a medical device) are rapidly emerging as clinically effective treatments for diverse chronic diseases. For example, the Food and Drug Administration (FDA) has recently authorized a prescription virtual reality (VR) app for treatment of moderate to severe low back pain. The FDA has also approved an adjunct digital therapy in conjunction with buprenorphine for the opioid use disorder, further illustrating opportunities to integrate digital therapeutics with pharmacotherapies. There are ongoing needs to disseminate knowledge about advances in digital interventions among health care professionals, policymakers, and the public at large. This mini-review summarizes accumulating clinical evidence of digital interventions delivered via virtual reality and mobile apps to improve opioid-based analgesia. We identified relevant randomized controlled trials (RCTs) using Embase and PubMed databases which reported pain scores with a validated pain scale (e.g., visual analog scales, graphic rating scale, numeric rating scale) and use of a digital intervention in conjunction with opiates. Among identified RCTs, the majority of studies reported improved pain scores in the digital intervention group, as compared to “treatment as usual” group. Our work suggests that VR and mobile apps can be used as adjunct digital therapies for pain management. We discuss these findings in the context of how digital health technologies can transform patient-centered pharmacy care.